Pengabdian Pendampingan UMKM dalam Membangun Branding Berbasis Pelestarian Lingkungan - Rizka Amelia; Ady Putra Musati; Rizki Amelia; Akmal Addaafi; Raja Ardhio Ramadhan; Marnida Delova; Siti Humayrah; Rini Elfina; Muhammad Yusuf (Lembaga Pengembangan Kinerja Dosen, 2026)
The Community Service College Program (KPM) is a form of student service aimed at making a real contribution to solving problems in the community. One of the issues found at the KPM site is the community's low awareness of keeping the environment clean due to limited trash disposal facilities. This activity aims to raise community awareness about the importance of maintaining environmental cleanliness through the distribution of trash bins. The method used is descriptive with a participatory approach, which includes observation, problem identification program implementation, and evaluation of the activity results. The results show that providing trash bins makes it easier for the community to dispose of garbage properly and encourages greater awareness of keeping the environment clean. This program has also received positive responses from the community because it is considered capable of supporting the creation of a cleaner, healthier, and more comfortable environment. In addition, this activity is expected to foster the habit of disposing of trash properly, increase community participation in maintaining public facilities, and create a culture of sustainable environmental care for all residents. Therefore, distributing trash bins is a simple yet effective effort to boost community participation in maintaining environmental cleanliness sustainably.